Logical Positivism in The Interpretation of The Al-Qur`an - Sukma Maulana (Indonesia); Hepni Putra/Co-Author (Indonesia); Muin Bensar (Filipina) (Mafatih, 2023)
The truth of the Qur’an is not only text but also context. Recently, many scientific researchers have tried to explore the truth of the Qur’an through a scientific approach as well. Tafsir scholars also do not miss out on contributing interpretations using a logical approach. There are still many orientalists or people who do not believe in the Qur'an who say that the Qur'an cannot be verified as scientific. This is interesting, because the issue of the originality of the Qur’an from time to time has always been a problem. The Qur'an talks about science, providing information that can be used as a reference for truth. Various methods of interpretation have been created to make it easier to understand verse by verse. One that is commonly used in interpretation is the bil al-ra'yi method, which is then a method that has similarities with the theory of logical positivism. This research uses the library research method by referring to tafsir books. Through the Logical Positivism method developed by philosophers, the truth of the Qur’an can increasingly be proven because this theory was created to provide an argument for truth through the principle of verification. In this research, the researcher only mentioned three of several verses from the Qur’an about science which were measured by Logical Positivism, namely about the creation of humans, the benefits of honey and sea water meeting fresh water.